2015
DOI: 10.18633/bt.v17i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Perkinsus Marinus en Crassostrea Gigas Y Chione Fluctifraga De Bahía De Kino, Sonora, México

Abstract: At present, the Pacific oyster Crassostrea gigas is the most cultivated shellfish in northwest Mexico. Nonetheless, other mollusks species such as the black clam Chione fluctifraga, which can be found along with cultured C. gigas in Sonora, represents a profitable emerging fishery resource. Since 1997, the oyster industry along the Gulf of California has been affected by severe mortality episodes disturbing almost all the farming areas. In order to evaluate the prevalence of Perkinsus marinus, a monthly sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
2
1
1
Order By: Relevance
“…While they are adults, their growth rate decreases, and the parasite can reach higher infection intensity, which is consistent with this work, because bigger oysters (>50 mm shell height) presented the highest prevalence and infection intensity of P. marinus. Contrary findings for other cultivated oyster species are reported by Enríquez-Espinoza et al (2015) and da Silva et al (2016), who found that infection rates were independent of oysters' size. According to Paytner et al (2010) and Ehrich & Harris (2015), larger oysters have a larger gill area that consequently leads to a higher filtration rate favoring infection through the increased ingestion of parasite cells, which could explain our results.…”
Section: Cácerescontrasting
confidence: 89%
See 1 more Smart Citation
“…While they are adults, their growth rate decreases, and the parasite can reach higher infection intensity, which is consistent with this work, because bigger oysters (>50 mm shell height) presented the highest prevalence and infection intensity of P. marinus. Contrary findings for other cultivated oyster species are reported by Enríquez-Espinoza et al (2015) and da Silva et al (2016), who found that infection rates were independent of oysters' size. According to Paytner et al (2010) and Ehrich & Harris (2015), larger oysters have a larger gill area that consequently leads to a higher filtration rate favoring infection through the increased ingestion of parasite cells, which could explain our results.…”
Section: Cácerescontrasting
confidence: 89%
“…Different Perkinsus-like parasites have been reported in wild and cultivated bivalve species in and around the Gulf of California using different techniques given their presence, detection, confirmation, and infection degree. For instance, P. marinus was found in natural populations of C. corteziensis on the central coast of the Mexican Pacific (Cáceres-Martínez et al, 2008) and the mangrove oyster Saccostrea palmula along the Sinaloa coast (Cáceres-Martínez et al, 2012), as well as in the wild population of the black clam Chione fluctifraga in Kino Bay, Sonora (Enríquez-Espinoza et al, 2015). Perkinsus sp.…”
Section: Introductionmentioning
confidence: 99%
“…Algunas teorías basadas en la combinación e interacción de factores extrínsecos (bióticos y abióticos) e intrínsecos (genéticos, inmunológicos y fisiológicos), son usadas frecuentemente para explicar la drástica reducción de bivalvos en cultivo (Royer et al 2007, Enríquez-Espinoza et al 2010. Derivado de esfuerzos coordinados del gobierno con los productores y centros de investigación para tratar de conocer las causas de mortalidad en C. gigas, se ha concluido que la presencia de patógenos (Enríquez-Espinoza et al 2010, Vázquez-Yeomans et al 2010, Enríquez-Espinoza et al 2015 y/o la combinación de parámetros ambientales (Chávez-Villalba et al 2007, Castillo-Durán et al 2010 pueden estar asociados a la reducción del cultivo. No obstante, la erradicación de los patógenos y el control de las condiciones del medio ambiente son tareas imposibles, por lo que la única opción para los productores parece ser el seguimiento de buenas prácticas de cultivo para minimizar el impacto de las mortalidades (Enríquez-Espinoza et al 2010).…”
Section: Introductionunclassified
“…In the Gulf of California, reported this protozoan in C. corteziensis, and Enríquez-Espinoza et al (2010) in C. gigas. Enríquez-Espinoza et al (2015) mention that this pathogen was found throughout the year in cultures of C. gigas and wild black clam Chionista fluctifraga with fluctuating prevalence and without mortality events. This pathogen has proven to be the most prevalent one in the south area where the higher temperature was presented compared to the north.…”
Section: Discussionmentioning
confidence: 97%